Developing A Framework Of Teaching And Learning Environments Using Multimedia: From Teacher-Centred, Student -Centred To Mixed-Mode Of Learning - Neo, Tse Kian (2007)
The research will seek to create a framework for learning and teaching environments in higher education , specially , when multimedia technology is used as a means of multiple media presentation tool, interactive learning tool and as a tool for students to construct knowledge in their learning process.